Artificial intelligence in digital marketing: methodology, advantages, and constraints - Demidova А. А. (НТУ "ДП", 2025)
Teams that used generative models in the ideation and copywriting stages reduced planning delays by 51%, but only achieved a 27% reduction in CPL when editors performed light proofreading; full automation further reduced editing time but doubled complaints about tone mismatch, increasing media spend. Personalization acted as a partial mediator, increasing CTR by 38% when the quality of the own data was above the 75th percentile. Trust in moderators affected cost effectiveness: the benefits disappeared when marketers expressed low confidence in machine outputs. Команди, які використовували генеративні моделі на етапах ідеації та копірайтингу, скоротили планувальні затримки на 51 %, проте досягли лише 27 % зниження CPL, коли редактори здійснювали легку перевірку; повна автоматизація ще більше зменшила час редагування, але подвоїла скарги на невідповідність тону, підвищивши медіавитрати. Персоналізація виступила частковим медіатором, підвищивши CTR на 38 % за умови, що якість власних даних перевищувала 75-й перцентиль. Довіра модератором впливала на ефективність витрат: переваги зникали, коли маркетологи висловлювали низьку впевненість у машинних виходах.
Штучний інтелект у цифровому маркетингу: методологія, переваги та обмеження
Keywords: artificial intelligence; virtual advertising; personalisation; performance; constraints; trust; SME.; штучний інтелект; цифрова реклама; персоналізація; ефективність; обмеження; довіра; МСБ